Perbaikan Kualitas Lempung Pundong - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRAK Pundong clay is high in plasticity, and this causes the clay cannot be made to ceramics easily. To improve that characteristic we can add non-plastic material such as sand to reduce plasticity. The addition of the sand to the clay makes melting point of mixture become higher than before. This is caused by the high melting temperature of sand. A substance as a flux is needed to reduce it. Another problem of the clay is its bad baked color. This problem can be dealt with coating the surface of ceramics by red clay suspension before baking stage. At the preparation stage, Pundong clay and sand were heated under the sunlight until fairly dry. The clay was then crushed and pulverized. After crushing process, it is sieved to get the 60 mesh product. The pulverized clay is then mixed with sand in various compositions from 0 to 40 % by volume. The mixture was added with the flux in the range from 1-4 %, and then baked from 600 °C. to 900 °C. This research has found that the highest strength of ceramics is achieved by 26.15 % addition of sand, with 1-2 % flux concentration and 900 °C. of baking temperature. Highest porosity is found at the temperature 600 °C, and the lowest porosity at 900 °C. Keywords: Lempung Pundong